THE INFLUENCE OF THE ENVIRONMENT TO MAGGIE S BEHAVIOR IN CRANE S MAGGIE: A GIRL OF THE STREET - Y. Sigar , Prawidya; Rorintulus, Olga; Lolowang, Imelda S. (English Education Department, 2020)
The purpose of this research is to reveal the influence of the environment to Maggie s behavior in Crane s Maggie: A Girl of the Streets In conducting this research in which the data are in the form of words rather than numbers In analysing the data the writer used objective and psychological approach The data collected in this research from two sources primary and secondary sources Primary sources is Crane s Maggie: A Girl of the Street and secondary sources are the other books and data from internet that related to this research The result of this research shows that Maggie has a miserable life that caused by her bad environment Caused by her family condition her job her neighbourhood her love relationship with Pete and all the problems that she has to face in everyday of her life But the conditions make her depressed At the end of the story Maggie chooses a wrong decision She kills herself < p>